Penerapan Akuntabilitas dan Transparansi Pengelolaan Alokasi Dana Desa Dalam Pembangunan Desa (Studi Kasus Desa Bungo Tanjung Kecamatan Tebo Ulu Kabupaten Tebo) - Muzakkir Mubarak (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2022)
Management of village fund allocation in village development in bungo tanjung villa overall, starting from accountability and transparency, it is quite good, but still has quite a lot of weaknesses and shortcomings. This is evidenced in the management of village fund allocations, the government has implemented the principle of accountability, namely by involving the community in planning the allocation of village funds (village deliberation), but only until the planning, the rest is carried out by the village goverment without involving the village community in managing the village funds.